A voz de tenor: bases históricas da pedagogia vocal a partir do Bel Canto até os conceitos metodológicos da atualidade - Nestor Ramon Cordero Gurry (2014)
Objective: This study has two goals: (1) to analyze the collected information from the Vocal Literature applied to the training of the tenor voice since the Bel Canto period. (2) To promote and stimulate ways to think about the current pedagogical tendencies to train the tenor voices during the first stages of their practice. Special attention is given to the anatomical and physiological foundation of the respiratory and fonatory systems. Methodology: This study deals with a qualifying method of investigation starting with digging in the Literature of the Singing Voice as well as the contributions gathered by means of observation and dialogical relationships with the voice professors from the Federal University of Minas Gerais and the State University of Minas Gerais. The application of a semi-structured interview was made on the content of the listed interviews. Results: The high range of the tenor voice must be approached in a soft and progressive manner. Never to rush or to force the chest voice into the head voice. Conclusion: There are two critical issues on training a tenor voice, the stable larynx position and the establishment of strategies to blend the chest register and the head register through the passaggio zone. These technical aspects must be carefully studied and worked by the teacher with every tenor he/she might have as a student.